Modern Problems of Education of Students in the Field of Education - Kholmatova Sh.M. Senior Lecturer (Western European Studies, 2024)
This article examines the modern problems of educating students that arise in the field of higher education. The emergence of socially vulnerable groups of youth and the simultaneous cultivation of the elitism of others led to the growth of individualism in its acute manifestations.
Keywords: upbringing; education; creative work